Developing Recommendation Website to Enhancing Promotional for Micro Small Medium Enterprises in Yogyakarta - Alfin Ahsanul Hakim; Adam Sekti Aji (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
The rapid advancement of technology has opened new opportunities for Micro, Small, and Medium Enterprises (MSMEs) to promote their products to a broader audience. This research aims to assist MSME owners in enhancing product promotion through the development of a social media-based website. The platform leverages user activity data to generate personalized product recommendations, helping businesses connect with potential customers more effectively. Key features of the website include viewing, liking, and commenting on user-uploaded content, as well as content upload capabilities. These features foster transparency in public opinion about MSMEs, enabling business owners to use feedback to improve product quality. The website was developed using the System Development Life Cycle (SDLC) with an Agile methodology, ensuring a systematic and iterative development process. This platform aims to provide promotional opportunities for MSME owners while also offering the community food recommendations in the Yogyakarta area.